Enflasyon Vergisi Üzerine Bir Analiz: KKTC Örneği - Akçaba, Soley (Muş Alparslan Üniversitesi, 2019)
Seigniorage is the difference between the value of themoney and production cost. Seigniorage income is what the Government earns viaits right to print money. Inflation tax is the loss of capital, due toinflation, of those who keep cash with themselves. The use of Turkish Lira(TRY) as official currency of Turkish Republic of Northern Cyprus (TRNC), because of the lack of emission authority of the Central Bank of TRNC can beclassified as dollarization. While the party with emission authority earnsseigniorage income, the other party is subjected to inflation tax due to lossin purchasing power of money in circulation. The aim of this study is toinvestigate the inflation tax that TRNC has been exposed to due to the use of TRYand to compare this with the aid received from Republic of Turkey in the sametime frame.

Senyoraj, paranın üretim maliyetiyle üzerindeki yazılı değer arasındaki farktır.  Senyoraj geliri, devletin para basma hakkınıelinde bulundurması neticesinde elde ettiği gelirdir. Enflasyon vergisi ise, enflasyon sebebiyle elinde para tutanların uğradıkları sermaye kaybıdır.  Kuzey Kıbrıs Türk Cumhuriyeti MerkezBankası’nın emisyon yetkisi bulunmaması nedeniyle resmi para birimi olarak TürkLirası’nı kullanması dolarizasyon kavramı olarak tanımlanır. Emisyon gücünesahip olan taraf para arzı ile senyoraj geliri elde ederken, dolarizasyonuuygulayan taraf ise dolaşımdaki paranın satın alma gücünün reel olarak azalmasısebebiyle enflasyon vergisine maruz kalır. Bu çalışma ile; Kuzey Kıbrıs TürkCumhuriyeti’nin Türk Lirası kullanımı nedeniyle maruz kaldığı düşünülenenflasyon vergisini yıllar itibariyle incelenmiş, ortaya çıkan bulguları, Türkiye Cumhuriyeti’nin aynı süreç içerisinde KKTC’ye yapmış olduğu yardımmiktarı ile karşılaştırmak suretiyle durum analizi yapılmıştır.
An Analysis on Inflation Tax: TRNC Case Study
anemon
Keywords: Seigniorage; Inflation tax; Dollarization; Money Supply; TRNC; Senyoraj; Enflasyo Vergisi; Dolarizasyon; Para Arzı; KKTC